Occupational qualifications: the elusive quest to connect education and work - Alphonsus, Naomi Sumangala (My University, 2024)
This thesis examines the state-led regulatory development of occupational qualifications and their intended curricula under the Occupational Qualifications Sub-Framework of the South African National Qualifications Framework. South Africa’s vocational education policy has seemingly shifted from an outcomes-based approach to a more integrated approach to training towards occupational qualifications. The main aim of the research is to analyse the standardised templates for the development of occupational qualifications and their intended curricula, with the view to evaluating whether they contribute to coherent qualification and curriculum development for vocational learning programmes. In so doing, the thesis draws on the literature on competency-based training (CBT) and on occupations. CBT prioritises task performance, with learning outcomes derived from standards and subsequently used to design curriculum content. While CBT advocates argue that students are better prepared for work if they can perform the tasks required in the work environment, critics highlight how a focus on task performance-based and assessment-led curricula in vocational education and training fragments learning by excluding disciplinary knowledge. The thesis develops the notion of occupational capacity as the requirement for expert practice, which emphasises that the relationship between training and practice in occupations is subject to two forces: an internal force of specialised knowledge, which encapsulates systematically organised knowledge, occupational practice, skill, and autonomy; and an external force in the form of the social organisation of occupations by professional bodies, institutions, and the state. The research uses a case-study methodology, thematically analysing the data from interviews, and documents on two occupational qualifications and their intended curricula: electrician and plumber. The analysis shows that occupational qualifications use the CBT approaches of learning outcomes and design down to derive curriculum content that prioritises task performance and compromises specialised knowledge. Additionally, the task performance-focused curriculum content is problematic for fragmenting the systematically organised, specialised knowledge that needs to be developed for expert practice, as a result of the state’s distorted version of work readiness (found in standardised templates and development processes) which lacks recognition of the social factors affecting the development of occupational capacity. Ultimately, I argue that vocational education policy seeking to shape occupational training needs to consider both specialised knowledge and the social organisation of occupations to fully engage with the development of occupational capacity for expert practice. ii The thesis makes two contributions. first, the research contributes to research uncovering the general principle of competency-based training approaches degrading curriculum. The analysis showed that occupational qualifications and their associated intended curricula relates to occupational standards, which are similar to but somewhat broader than learning outcomes that are designed down into guidance for curriculum content. Second, the research makes a theoretical contribution by strengthening our conceptual understanding of occupations through the development of an occupations conceptual web. In contrast to task-based CBT approaches, the occupations conceptual web centralises occupational capacity based in specialised knowledge and the social organisation of occupations that foregrounds training for expert practice.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Education, University of the Witwatersrand, Johannesburg, 2022
Keywords: Occupational qualifications; South African National Qualifications Framework; Curricula